The ImpactOf Promotion Mix On Customer Purchasing Behavior- Umniah Company- (Revue El-Wahat pour les Recherches et les Etudes, 2016)
This study aimed to evaluate the extent of the effectiveness of the promotion element effort which are provided by Umniah Company and understand how all these elements come together to create tends of customers or influence their purchase behavior.A sample was taken from the population of Irbid City, the study indicate the following results:                             • There were positive perceptions among the majority of the sample about elements of promotion which are applied by Umniah Company.• There were significant differences among the elements of promotioninfluencing in customer purchase behavior.• Finally, it was found that the most important promotional methods used were : advertise and sales promotion.Keywords: Marketing Mix, Promotion Mix, Customer Purchase Behavior, Umniah Company                                                                       .